The inferior olive of the C57BL/6J mouse: a chemoarchitectonic study - Yu, You; Fu, Y.; Watson, Charles (John Wiley & Sons, 2014)
We have used the histochemical and immunohistochemical staining methods and maps of gene expression to analyze the structure of the inferior olive of the C57BL mouse. As in other mammals, the inferior olive of the C57BL mouse contains three major nuclei, the medial nucleus, the principal nucleus, and the dorsal nucleus. The medial nucleus can be divided into a rostral medial nucleus and a more complex caudal part, which is formed by subnuclei C, B, A, the cap of Kooy, and the beta subnucleus. The principal nucleus includes the major principal nucleus and the arcuate subnucleus. Most of the inferior olive neurons are small to medium size, the smallest of which are found in the arcuate subnucleus. Calbindin and the vesicular glutamate transporter 2 gene are expressed in nearly all inferior olive neurons, but acetlycholinesterase, glutamate decarboxylase 1 gene, cocaine- and amphetamine-regulated transcript protein prepropeptide gene, galanin gene, and calretinin are selectively expressed within different subnuclei. These findings are consistent with a pattern of extensive functional differentiation among the neuron groups of the inferior olive.